The extent of employment of the constructivist approach on teaching of the grammatical concept from the point of view of teachers of Arabic Language in Jenin Governorate - Al-Saabneh, Amna Fathi; Habayeb, Ali Hassan (Journal of Educational and Psychological Sciences, 2022)
This study aimed to investigate the extent of employment of the constructivist approach on teaching of the grammatical concepts from the point of view of teachers of Arabic Language in the Jenin Governorate. To achieve the purposes of the study the researcher followed descriptive analytical method, and a questionnaire was prepared as a tool to collect the data. The researcher checked its validity and reliability. The questionnaire was applied to the study sample which consists of (93) male and female teachers, and those who were selected by the stratified random sampling method from the study population represented by all teachers of the Arabic language in Jenin Governorate. The results of the study showed that: The total score for the level of employment of constructive approach in teaching grammatical concepts among Arabic teachers in the governorate of Jenin was (4.428) and the relative weight (88.56%). The field of educational activities was ranked first degree, with a relative weight (91.32%) of. The planning field came in second degree, weighing 91.02%. The field of educational methods was ranked third degree, with a relative weight (90.66%), while the area of evaluation was fourth degree, with a relative weight (82.82%). Also results of the study showed a statistically significant differences at (α≤0.05) in the means of employing the constructive approach in teaching grammatical concepts, according to gender in favour of female teachers and according to school stage in favor of elementary stage. There are no statistically significant differences at (α≤0.05) in the means of employing the constructive approach in teaching grammatical concepts, according to academic degree, teaching experience and school gender. In light of the current study findings, the researcher offers the following recommendation: Preparation of a training program to develop the proficiency of Arabic language teachers in the light of structural theory. Provide means of support to encourage teachers to use teaching strategies based on construction theory. That curriculum developer develop language syllabuses based on constructivism theory.
Keywords: Constructivist Approach; Grammatical Concepts; Teachers of Arabic Language